Considerations for Using Research Data to Verify Clinical Data Accuracy - Fort, Daniel (AMIA Jt Summits Transl Sci Proc, 2014)
Collected to support clinical decisions and processes, clinical data may be subject to validity issues when used for research. The objective of this study is to examine methods and issues in summarizing and evaluating the accuracy of clinical data as compared to primary research data. We hypothesized that research survey data on a patient cohort could serve as a reference standard for uncovering potential biases in clinical data. We compared the summary statistics between clinical and research datasets. Seven clinical variables, i.e., height, weight, gender, ethnicity, systolic and diastolic blood pressure, and diabetes status, were included in the study. Our results show that the clinical data and research data had similar summary statistical profiles, but there are detectable differences in definitions and measurements for individual variables such as height, diastolic blood pressure, and diabetes status. We discuss the implications of these results and confirm the important considerations for using research data to verify clinical data accuracy.